(untitled) (Eureka Journal of Language, Culture & Social Change, 2026)
The current research addresses the study of critical thinking and its relationship with sustainable behavior among students of the College of Basic Education at the University of Misan, through five main objectives: identifying the level of critical thinking, revealing the significance of differences in it according to gender, examining the level of sustainable behavior, determining the significance of differences in it according to gender as well, and ultimately clarifying the nature of the correlational relationship between the two variables. The researcher relied on the descriptive correlational method, and the research sample consisted of 200 male and female students selected using the stratified random method from the Departments of Science, Mathematics, Arabic Language, and Primary Class Teacher, with 50 students from each department equally distributed between males and females. Watson and Glaser’s Critical Thinking Scale in its Arabic version and the Sustainable Behavior Scale adapted for the Arab environment were utilized. The research results revealed that the level of critical thinking among the sample individuals was average, while the level of sustainable behavior was below average. The differences in critical thinking between genders were not statistically significant, whereas the comparison between genders in sustainable behavior showed statistically significant differences in favor of females.